Practices causing time delay in seeking care for mental illness - Kandasamy, Sunitha; Vijayalakshmi, M.; Buhari, Abdulrahuman Mohamed (International Journal Of Community Medicine And Public Health, 2019)
Background: Mental health is the foundation for wellbeing and effective functioning for an individual. When people consult clinicians to determine the cause and treatment for such illness, they may also seek answers to questions that medical science can’t answer. Many patients rely on a religious or traditional framework to help answer these questions that often hinder medical treatment and affect its prognosis. This study aim to estimate the practices adopted by the community for cure of mental illness and estimates the time delay that occurred to initiate medical treatment because of these practices. Methods: A cross sectional study was conducted among 103 patients and their caretakers undergoing treatment in the Psychiatry Department of a tertiary care hospital using a semi structured questionnaire. The data collected was analyzed for mean and statistical significance between proportions. Results: Among the 103 patients, 54.4% were males and 45.6% females. 54.3% of patients suffered from psychosis and 45.6% from neurotic illness. About 60.1% of the patients had experienced some form of traditional and religious practices for treating their illness before approaching medical treatment causing an average time delay of 2.6 years to initiate regular medical treatment. Conclusions: The high rate of religious and traditional practices followed by the community for psychiatric illness leads to significant time delay in initiating evidence based management of illness resulting in significant reduction in the quality of life of these patients. Hence mental health awareness initiative at community level and strengthening mental health services at primary care level is the need of the hour.